Recommendations for COPD management in Central and Eastern Europe - Valipour, Arschang; Aisanov, Zaurbek; Avdeev, Sergey; Koblizek, Vladimir; Kocan, Ivan; Kopitovic, Ivan; Lupkovics, Gergely; Man, Milena; Bukovskis, Maris; Tudoric, Neven; Vukoja, Marija; Naumnik, Wojciech; et al. (Expert review of respiratory medicine, 2022)
INTRODUCTION: The Global Initiative for Chronic Obstructive Lung Disease (GOLD) strategy report provides guidance on effective management of chronic obstructive pulmonary disease (COPD) according to local healthcare systems. However, COPD is a heterogenous disease and certain aspects, including prevalence, disease-time course and phenotype distribution, can differ between countries. Moreover, features of clinical practice and healthcare systems for patients with COPD can vary widely, even in geographically close and economically similar countries. AREAS COVERED: Based on an initial workshop of respiratory physicians from eleven countries across Central and Eastern Europe (CEE) in December 2018 and subsequent discussions, this article offers region-specific insights from clinical practice and healthcare systems in CEE. Taking recommendations from the GOLD 2022 report into account, we suggest approaches to adapt these into national clinical guidelines for COPD management in CEE. EXPERT OPINION: Several factors should be considered when optimizing management of COPD in CEE compared with other regions, including differences in smoking status, vaccination uptake, prevalence of tuberculosis and nontuberculous mycobacteria, and variations in healthcare systems. We provide guidance and algorithms for pharmacologic and non-pharmacologic management of COPD for the following scenarios: initial and follow-up treatment, treatment of patients with frequent exacerbations, and withdrawal of inhaled corticosteroids where appropriate.
Keywords: pharmacologic management; Disease Progression; Europe; progrese nemoci; non-pharmacologic management; Evropa; Chronic obstructive pulmonary disease; algorithms; fenotyp; Pulmonary Disease, Chronic Obstructive; exacerbations; chronická obstrukční plicní nemoc; clinical guidelines; Phenotype; Humans; Central and Eastern Europe; inhaled corticosteroids; hormony kůry nadledvin; Adrenal Cortex Hormones; lidé